ANALYSIS AND IMPACT OF LEAD-CONTAINING WASTE FROM LEAD PRODUCTION ON HUMAN LIFE AND THE ENVIRONMENT - Zarina Bagova; Kurmanbek Zhantassov; Gaukhar Turebekova; Bayan Sapargaliyeva (Academic Journal of Physical and Chemical Sciences, 2021)
As a result of the activities of the lead plant, about 2 million tons of waste in the form of leadcontaining slags were accumulated. Lead production slags contain a large number of toxic heavy metal compounds, such as lead, zinc, osmium, and cadmium, which are dangerous sources of environmental pollution. Due to the open storage of slags, there is an excess of the maximum permissible concentrations (MPC) of lead: near the plant, the concentration of lead is more than 3000 mg/kg in the soil, with a MPC of 3.2 mg/kg. Lead and zinc compounds are dangerous to humans due to their significant toxicity and ability to accumulate in the body. Lead poisoning ranks first among professional intoxications. Waste water containing zinc compounds is not suitable for irrigation of fields, the negative effect of zinc compounds on microorganisms and microfauna of the soil reduces its fertility. The article presents the results of scientific studies of lead slag, conducted by scanning electron microscopy and X-ray microanalysis, performed on a scanning electron microscope (SEM) JEOL-6490 LV (Manufacturer: JEOL, Japan). The results of the thermal analysis of samples on the derivatograph of the F. Paulik, J. Paulik and L. Erdey system in the air environment, in the temperature range of 20-1000°C. are presented. According to the results of research, it was found that lead slags contain a sufficiently high amount of nonferrous metal compounds: lead oxide up to 0.7 % and zinc oxide up to 8.5 % of the weight amount of slag, which makes the process of recycling toxic waste from lead production technically and economically feasible.